A Research on the Use of Waste Mandarin Peels as Fixing Agents in Leather Production and Its Effects on Ageing and Colour - Eser Eke Bayramoglu; Fatma Coşkun Topuz; Mehmet Münir Ayana; Samet Soylu (Turkish Journal of Agriculture: Food Science and Technology)
In this research, the effect of extract obtained from waste mandarin peels on inhibition or retardation of ageing of the leather was investigated. Firstly, mandarin peels were extracted and antioxidant activity of the mandarin peels were detected by using of DPPH method. This antioxidant method is based on DPPH that is a purple stable compound, inhibition with sample compound. Extracted mandarin peel samples were read by spectrophotometer at 517 nm wavelength. At final, antioxidant activity of mandarin extract was determined as 65 µM TE/g. The mandarin extract treated with leather after formic acid fixation as a fixator. Goat leathers were kept under 80°C/UV for 72 hours for aging process and the colour values of initial and hindermost leathers were measured with using of Konica Minolta CM 3600d Brand spectrophotometer. L*, a*, b* and ΔE values of the samples were calculated. At the end of the study, it was found that mandarin extract was a natural antioxidant and if it was used as a fixator it could have aging retardant effect at the leather production. Also, it was determined that the use of waste mandarin peels extract increases the brightness of the leather. The difference between the colour values of the leather samples in which the extract was used and not used was found statistically significant.